Create Brand Attractiveness to Support Attracting Strategy by Using Employee Value Proposition (Case Study in PT. Dirgantara Indonesia (Persero)) - Febriana, Unggaran; Welly, John (The Indonesian Journal of Business Administration, 2013)
Half of the total employees of PT. Dirgantara Indonesia almost and already in retirement, especially for engineers almost half of the total engineers no longer an employee of PT. Dirgantara Indonesia, because they actually have long retired. That happened becausethe customers PT. Dirgantara Indonesiaprefere to choose a retired senior engineers to run their projects. This will cause obstacle in the transfer of technology, knowledge and expertise. This situation going worst with recruitment activities undertaken by PT. Dirgantara Indonesia are not going well it can be seen from the data of total applicants in 2011 fell as much as 1:5 to 1:3 in 2012 make PT. Dirgantara Indonesia have a difficulty to regenerate the engineers and other employees in general. The declining number of applicants due to low employer brand ofPT. Dirgantara Indonesia. To be able to create an employer brand that appeal to prospective employees can be used EVP models. Before using the model, first we need to know the employee value proposition in PT. Dirgantara Indonesia. From the observations and discussions with the expert form PT. Dirgantara Indonesia, employee value proposition in PT. Dirgantara Indonesia is leadership, work, performance evaluation, reward, and company. From the analysis that has been done, there a five solution to build the EVP. But because there are a lot of constraints and limitations in the implementation of five improvement areas, PT. Dirgantara Indonesia can run first the most critical areas and provide significant impact and also can respond to the problems PT. Dirgantara Indonesia. Policy is very important to address the issue of transfer of technology, knowledge and skills. And then training and development is important because based onpre-research result training and development is the most important preferences for the job seekerÂ Keywords: EVP, Employee Value Proposition model